Identifying Awareness Requirements in Face-to-Face Collaborative Applications for Users with Autism Spectrum Disorders - Silva, Greis F. Mireya; Raposo, Alberto Barbosa (Anais do Simpósio Brasileiro de Sistemas Colaborativos (SBSC); 2016: Anais do XIII Simpósio Brasileiro de Sistemas Colaborativos, 2016)
Individuals with Autism Spectrum Disorders (ASD), mainly those with high severity, have difficulties to identify and understand the others’ actions and emotions and, therefore, to understand the basic concepts of a collaborative work, even in face-to-face situations. We developed and evaluated a multitouch collaborative game with youths with high severity in ASD. Despite the positive results to encourage the social interaction, we observed that they had difficulties to understand tasks, to identify their partners, and the workspace. Based on these difficulties, we identify a set of awareness requirements to contribute to the design of awareness mechanisms adequate to face-to-face collaborative applications for individuals with ASD.